Time-frequency analysis of freqency-hopping signals based on sparse recovery - Zhi-chao SHA; Zhi-tao HUANG; Yi-yu ZHOU; Jun-hua WANG (Tongxin xuebao)
To overcome the common shortcomings shared by the existing methods: weak suppression noise interference and feeble performance of time-frequency concentration,a novel time-frequency analysis method based on sparse repre-sentation was developed,which could get clear and concentrate time-frequency representation.Firstly,the unconstrained sparse representation model of FH signals was established according to the punish function theory.Then,the guideline of punish parameters were analysed theoretically and got time-frequency representation by sloving the optimization problem used approximate l0norm finally.The simulation results show that this method is capable of getting clear time-frequency pattern.